Goji Berry: nutritional properties and benefits for human health (Research, Society and Development, 2019)
Lycium barbarum (Goji Bery) is a plant belonging to the family Solanaceae, is used as functional food in several countries of East Asia, Europe and North America, is highly nutritious, having eight essential amino acids, minerals such as iron, zinc and selenium and antioxidant action. The objective of the article is to investigate the possible nutritional properties of Goji Berry and its benefits to human health. It is an integrative review, after surveying the articles following the pre-established inclusion criteria, a total of 13 studies published in the last ten years were obtained. The great majority (78%) of the experimental studies show positive effects for the use of Goji berry. However, adverse effects exist and depending on the use, can be considered a risk to public health, therefore, caution and professional guidance regarding the safe consumption of this food must be taken, in order to avoid adverse effects, toxicity, allergies and consequences of their consumption on too much, especially in pregnant women, seniors and children.